Advances and challenges in the treatment of acute lymphoblastic leukemia in children: Perspectives from a national reference center in Peru - Alarcón-León, Sandra (2024)
The Instituto Nacional de Enfermedades Neoplásicas (INEN) is a national reference center in Peru where the largest number of pediatric patients with acute lymphoblastic leukemia (ALL) are treated. Methods: Patientes ages 1 to less than 15 years with diagnosis of ALL who received treatment according to the modified 2002 intercontinental Berlin-Frankfurt-Münster (IC-BFM) ALL protocol. Risk stratification was based on age, leukocyte count, extramedullary involvement (CNS, testicular), genetics, and response to initial treatment. Results: From 2014 to 2017, 652 patients were treated, which included 113 with lowrisk ALL, 120 with intermediate-risk ALL, 308 with high-risk ALL, and 103 with very high-risk ALL. The mortality rate during induction was 4.9%, and the remission rate was 90.8%. The abandonment rate was 25.6%. Event-free survival and overall survival at 5 years were 62.9%±4.1% and 63.7%±3.9%, respectively. Conclusions: It is essential to disseminate information that emphasizes the importance of ALL in the pediatric population, promoting early suspicion at the first level of care and facilitating timely referral to specialized centers.